Estrategias metodológicas activas, en base al arte musical, para el aprendizaje de la historia en el primer año de bachillerato general unificado - Vargas Murillo, José Carlos (2021)
The research work: "ACTIVE METHODOLOGICAL STRATEGIES, BASED ON MUSICAL ART, FOR LEARNING THE HISTORY IN THE FIRST YEAR OF UNIFIED GENERAL BACCALAUREATE." Focused on the study of history through the use of musical art in students of the first year of high school, it was a process of search and appreciation of art that is embodied in our society. Methodological strategies try to assist in the study of history by means of a structure that first analyzes the environment that promotes disinterest in class and distractors that cause the deficiency in the study; After that, the didactic elaboration of the methodological strategy that applies certain musical aspects to the historical development would be continued, then giving an evaluation and feedback to the socialized. Different opinions were collected through interviews to teachers who share the subject of history and through surveys aimed at students of the first year of baccalaureate of the Unidad Educativa “Gabriela Mistral”of the Latacunga city, Cotopaxi province. The result of these instruments determined the problem in the learning process, the lack of resources and methodologies used in class; In addition, the point of view of each one was appreciated for an implementation of musical art for historical learning and an interest was appreciated, as they require adequate methodologies and strategies to be able to teach and learn through musical art through history, since they accepted the proposal raised in a positive way.